Efektivitas Pengaruh Besaran Biaya Promosi Dalam Penghimpunan Dana Pihak Ketiga - Puji Lestari (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2009)
Effectiveness The Promotion Cost in Fundrasing the Third Party FundsPromotion is one important variable in marketing mix to promote the services. The promotion activities is not just as the communication tools between company and consumers, but also as the tools to influence the purchase behavior from the consumer to but the services that offered by the company. This things has done by the promotion tools. DOI: 10.15408/aiq.v1i2.2461